Corporate governance mechanism in dynamic global markets - Himachalam Dasaraju (Discovery Publishing House Pvt Ltd, 2015)
This book primarily focuses on the Corporate Governance (CG) in emerging economies, which is the driving force for corporate performance and overall economic prosperity, which is a dire need of the day in view of the global market environment. It generates interest in the structure and the status of CG practices in emerging economies, particularly India, which is recognised as one of the fast growing economies in the world. The corporate sector in India would remain changing and moving ahead as per the developments that were taking place in the other counterparts and developed economies like the US, UK and other parts of the corporate world.